Gut microbial metabolite indole-3-propionic acid inhibits inflammation and restores blood-milk barrier in S. aureus- induced mastitis by targeting aryl hydrocarbon receptor - Zhao, Lihua; Jin, Lei; Fu, Yunhe; Yang, Bin (Frontiers in Microbiology, 2025)
BackgroundIndole-3-propionic acid (IPA) is a tryptophan metabolite produced by intestinal bacteria, which has functions such as penetrating tissue barriers and reducing tissue inflammatory reactions. In the present study, the therapeutic effect of IPA on Staphylococcus aureus (S. aureus)-induced mastitis was investigated.MethodsA mouse model of mastitis was established using breast injection of S. aureus. Except for the control group, all other mice were given oral administration of IPA. Hematoxylin eosin (H&E) staining was used to detect pathological changes in mouse mammary tissue. ELISA was used to detect TNF-α and IL-1β levels. Western blot was used to detect protein expression.ResultsAs the results demonstrated, IPA treatment obviously attenuated S. aureus-induced mammary pathological injury, myeloperoxidase (MPO) activity, malondialdehyde (MDA) content, TNF-α, and IL-1β levels. Meanwhile, IPA treatment could restore blood-milk barrier, as confirmed by up-regulating the expression of ZO-1 and occludin. In vitro, IPA could inhibit TNF-α and IL-1β production and the activation of NF-κB and NLRP3 induced by S. aureus. Furthermore, IPA could increase the expression of aryl hydrocarbon receptor (AhR). In addition, the inhibition of IPA on S. aureus-induced inflammation was reversed by AhR inhibitor.ConclusionIn conclusion, the results suggested that IPA inhibited S. aureus-induced mastitis through inhibition inflammation and restoring blood-milk barrier by activating AhR.